Synergistic Potential Of Bioactive Compounds Of Nut Grass Tuber Extract (Cyperusrotundus) As Anti-Leukemia Herbal Medicine - Tri Aini Fadjrin Juliani; Nimim; Agustini, S. M.; Patmawati (Universitas Muhammadiyah Malang, 2021)
Leukemia treatment strategies have developed rapidly. Both the intensity of the dose and the duration of intensive treatment have been maximized after decades of trials optimizing chemotherapy options, dose intensity, and duration of treatment. The emergence of multidrug-resistant cancer cells (MDR) results in the higher costs needed in the treatment of AML patients. The purpose of this study was to identify and evaluate the potential of active compounds from Cyperus rotundus on the activity of the Acute Myeloid Leukemia (AML) cell line HL-60 APL through inhibition of proliferation, cell cycle, differentiation, and induction of apoptosis in the treatment of AML. The bioavailability of the compound to be taken orally was analyzed by Human Intestine Absorption (HIA+). Potential pathways inhibiting proliferation, cell cycle, differentiation, and induction of apoptosis in the treatment of AML were analyzed using a Structure-Activity Relationship approach with the PASS SERVER program. Pathway analysis was carried out using STITCH and Cytoscape v.3.5.1 programs. The study results showed that nutgrass has six active compounds quercetin, luteolin, apigenin, camphor, sitosterol, and gallic acid, synergizing the main pathway of cell activity (Pa>0.7).Conclusion of Cyperus rotundus extract has a high potential synergistically as an anti-leukemia herbal medicine.